Analyzing Modes of Foreign Entry. Greenfield Investment versus Acquisition - Thomas Müller (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2001)
This paper studies the entry decision of a multinational enterprise into a foreign market. Two alternative entry modes for a foreign direct investment are considered: Greenfield investment versus acquisition. In contrast to existing approaches, the acquisition price and the profits under both entry modes are endogenously determined. Interestingly, we find that the optimal entry mode decision is a ected by the competition intensity in the market in a non-monotonic way. When markets are very much or very little competitive, greenfield investment is the optimal entry mode, while for intermediate values it is acquisition.
urn:nbn:de:bvb:19-epub-13-9
Keywords: D43; F21; F23; L13; P31; 330; Foreign direct investment; multinational enterprise; greenfield investment; acquisition; transition economies